ChemInform Abstract: Two New Secondary Metabolites from the Fruits of Mangrove Avicennia marina. Issue 4 (January 2016) - Yan, Dong‐Mei; Gao, Cheng‐Hai; Yi, Xiang‐Xi; Xie, Wen‐Pei; Xu, Ming‐Ben; Huang, Ri‐Ming
Abstract: isolation and structure elucidation of maricaffeolylide A (I) and maricyclohexene A (II)